Graft versus host disease after multivisceral transplantation: A UK center experience and update on management. Issue 5 (16th April 2018) - Sharkey, Lisa M.; Peacock, Sarah; Russell, Neil K.; Middleton, Stephen J.; Butler, Andrew J.
Abstract: Graft versus host disease (GVHD) following transplantation of an intestine‐containing graft occurs more frequently than with other solid organ transplants and is known to have a poor outcome. The presentation differs from other solid organ transplants, as the gastrointestinal tract is not involved following intestinal transplant. Diagnosis is based on clinical symptoms arising due to native tissue damage and the detection of donor T lymphocytes in circulating blood (T‐cell chimerism). The ideal treatment strategy has not been defined, with advocates for both increased and decreased immunosuppression. We reviewed all cases of GVHD in an adult intestinal transplant center in the United Kingdom and report on management strategies of five cases and methods of detecting T‐cell chimerism. The practice in our center has evolved with experience. The first two patients received an increase in immunosuppression, which was only successful in one case. Subsequently, reducing immunosuppression has been more effective. However, patients with bone marrow involvement have a poorer prognosis. We demonstrate successful treatment of GVHD after multivisceral transplant with a reduction in immunosuppression. This should be followed by vigilant graft surveillance and serial monitoring of the level of T‐cell chimerism, with reintroduction of immunosuppression at the earliest sign of graft dysfunction.